PENGARUH MEDIA PEMBELAJARAN FLASHCARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN KELAS 1 SEKOLAH DASAR - Nur Rohmah, Aiza; Galuh Kartika Dewi; Satrio Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education must be packaged creatively and innovatively following current developments. One learning media that has interesting results for researchers is Flashcards. This research aims to determine the effect of Flashcard learning media on reading ability at the beginning of 1st grade of elementary school. This type of research is experimental research using a pretest posttest control group design. The population in this study were 1st grade students at Antawirya islamic Javanesse School. Learning outcomes are the results achieved by students in an effort to master learning at school. It is hoped that with Flashcard media students can easily understand the learning material in chapter V. This research was conducted on 1st grade students at Antawirya islamic Javanesse School. By involving group A, 23 children as the experimental class and group B, 23 children as the control class. From the results of the trial, students in class 1st grade of Antawirya islamic Javanesse School produced effective learning results, namely 72.5 in the pretest and 81.9 in the posttest. The research results of Flashcard media are suitable for use and improve learning and improve reading ability and student response questionnaire results with an average value of 76% or the flashcard media is categorized as good outcomes for grade 1 students at Antawirya islamic Javanesse School .